The Mirage of Overproduction in Spanish Cinema: A Critical Analysis of the Impact of Audiovisual Policies - Yébenes Cortés, María Pilar; Pradana Pérez, Francisco José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Despite a stable market share, the Spanish film industry suffers from an overproduction that threatens its competitiveness. Through a comparative analysis of production, box-office, and genre data, this study reveals a critical gap between film promotion policies and market demand. Public funding is concentrated on genres with limited commercial appeal, overlooking the proven success of animation, thrillers, and comedies. We conclude that the system must be urgently reformed, redistributing resources towards fewer productions with greater commercial viability in order to strengthen the industry's sustainability.